Potential Role of Myeloid-Derived Suppressor Cells (MDSCs) in Age-Related Macular Degeneration (AMD) - Kauppinen, Anu; Kaarniranta, Kai; Salminen, Antero (Frontiers in Immunology, 2020)
Myeloid cells, such as granulocytes/neutrophils and macrophages, have responsibilities including pathogen destruction, waste material degradation, or antigen presentation upon inflammation. During persistent stress, myeloid cells can remain partially differentiated and adopt immunosuppressive functions. Myeloid-derived suppressor cells (MDSCs) are primarily beneficial upon restoring homeostasis after inflammation. Due to their ability to suppress adaptive immunity, MDSCs can also ameliorate autoimmune diseases and semi-allogenic responses, e.g. in pregnancy or transplantation. However, immunosuppression is not always desirable. In certain conditions, such as cancer or chronically inflamed tissue, MDSCs prevent restorative immune responses and thereby aggravate disease progression. Age-related macular degeneration (AMD) is the most common disease in the Western countries that severely threatens the central vision of aged people. The pathogenesis of this multifactorial disease is not fully elucidated but inflammation is known to participate in both dry and wet AMD. In this paper, we provide an overview about the potential role of MDSCs in the pathogenesis of AMD.